DIFFERENCES IN WORKERS' BLOOD PRESSURE DUE TO NOISE IN THE MANUFACTURING INDUSTRY IN EAST JAVA, INDONESIA - Virrarny Eka Novyra; Ratih Damayanti; Ratnaningtyas Wahyu Kusuma Wardani; Indah Lutfiya (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Continuous noise exposure can cause an increase in blood pressure and work-related stress in the rotary production area of PT APB Manufacturing Industry in East Java Province, Indonesia. Purpose: This research aims to analyze the effect of noise intensity on blood pressure before and after work among employees in the rotary production area of the manufacturing industry in East Java Province, Indonesia. Method: This research employed an analytic observational study with a cross-sectional design. The sample, obtained through cluster random sampling, consisted of 49 people. Data were collected by measuring noise intensity and monitoring blood pressure before and after work. A Paired Sample T-test was conducted to assess differences in workers' blood pressure before and after exposure to noise. Result: Significant differences were observed in both systolic (p-value = 0.000) and diastolic (p-value = 0.010) blood pressure before and after work. Conclusion: Increased blood pressure appears to be linked to noise levels in the workplace exceeding the threshold value. Consequently, there is a need for control efforts to overcome this issue.